Women Entrepreneurs In A Patriarchal Society: Socio-Cultural Preceptions Of Women In Beer Parlour Business In Ibadan, Nigeria - Adenugba, Adebimpe A.; Oladeji, Tomilola; Akhuetie, Ruth (Advances in Social Sciences Research Journal, 2018)
The number of businesses owned and controlled by women all over the world has continued to rise steadily. However, women entrepreneurs still have to deal with issues relating to their gender as well as acceptance in the society. This study examines the socio-cultural perceptions of women in beer parlour business in Ibadan, Oyo State, Nigeria. The liberal feminist theory was adopted as the theoretical framework for this study. The exploratory survey design was used to collect data from the respondents and the questionnaire as well as in-depth interview formed the instruments for data collection in this study. Both descriptive and inferential statistics such as frequencies and percentages as well as the chi-square served as the data analytical tools. The study concluded that there is no significant association between respondents’ age, educational level, marital status as well as religious affiliation and perception towards women in beer parlour business. As a result, it has become imperative to discourage stereotypical perceptions in the society particularly of women in some certain trades.